The impact of urban spatial configuration on carbon emissions: Towards spatial planning for low-carbon development - Bo Wan; Yuhan Sun; Ningjie Shen; Qiang Sheng; Tao Yang (Sustainable Futures)
Urbanization and spatial planning are at the heart of global climate mitigation efforts, yet their direct influence on carbon emissions remains underexplored. This study systematically examines the impact of urban spatial configuration on carbon emissions across China's 2,470 county-level administrative units from 2007 to 2017. Leveraging a multi-scale spatial analysis framework and linear regression modeling, we reveal that spatial structure variables significantly enhance the explanatory power of traditional carbon emission models based on economic and demographic indicators. Our findings highlight that: (1) four spatial structure indicators—Integration Segment Length Weighted at 30 km (INT_SLW_R30 km), Normalized Angular Integration at 200 km (NAIN200 km), Spatial Influence at 10 km (SIF_R10 km), and Segment Lengths at 5 km (SL_5 km)—demonstrate strong and stable correlations with carbon emissions, explaining an additional 23.9 % variance beyond GDP and population factors; (2) high spatial integration at a meso‑scale (30 km) is associated with lower emissions, suggesting that compact urban configurations enhance efficiency and sustainability; (3) however, increased spatial influence at smaller scales (10 km) correlates with higher emissions, indicating that high-density, high-mobility zones may intensify energy consumption; and (4) metropolitan areas exhibit stronger spatial dependencies in carbon emissions, reinforcing the need for integrated regional planning. These insights underscore the pivotal role of spatial configuration in shaping urban carbon footprints and offer compelling policy recommendations: prioritizing compact urban forms, enhancing regional coordination, and aligning transport infrastructure with spatial hierarchy to optimize emission trajectories. Our research provides robust empirical evidence to inform spatial planning policies aimed at balancing economic growth with sustainability goals, positioning urban form as a central lever in global carbon mitigation strategies.